Women's worries about prenatal screening tests suspected of fetal anomalies: a qualitative study - Seyyedeh Mahboubeh Mirtabar; Zeynab Pahlavan; Sajedeh Aligoltabar; Shahnaz Barat; Fatemeh Nasiri-Amiri; Maryam Nikpour; Fereshteh Behmanesh; Sina Taheri; Khadijeh Nasri; Mahbobeh Faramarzi (BMC, 2023)
Abstract Background Pregnant women with suspected fetal anomalies experience a great deal of stress following prenatal screening tests. The present study aimed to investigate women's worries about prenatal screening tests suspected of fetal anomalies. Methods Through the use of qualitative content analysis, the reports of women whose prenatal screening tests were suspected of fetal anomalies were analyzed and the results were interpreted. The participants were selected from four public and private maternity care clinics of Babol, Iran, from December 2021 to January 2022, using targeted convenience sampling. Data were collected from 20 women aged 24 to 41 years old, who underwent prenatal screening tests and were suspected of fetal anomalies, using semi-structured face-to-face interviews. Results The four main themes included the "causes of worries" (with sub-themes of challenge with spouse and relatives, medical diagnosis processes, previous unpleasant experiences, physical and mental problems, financial worries, and misinformation), "anxiety-coping styles" (with cognitive emotion-oriented, behavioral emotion-oriented, and problem-oriented sub-themes), "reactions to a possible diagnosis of anomaly" (with three sub-themes, namely concealment, extreme fear and worry, and denial), and "attribution of the cause of the anomaly" (with sub-themes of consanguine marriage, evil eyes, tendency to have a baby of a particular gender, a history of anomalies in the previous child, the spouse's medical illness, unplanned pregnancy, and high maternal anxiety). Conclusion Women with suspected fetal anomalies experience a great deal of stress, the most important reason for which is the "physician's uncertainty". "Sharing worries with relatives" was the most common style of coping with worries. Establishing emotional support and empathetic communication between midwives and physicians with pregnant women suspected of fetal anomalies were important ways to reduce their worries.